Extended spectrum beta lactamase producing organisms causing urinary tract infections in Sri Lanka and their antibiotic susceptibility pattern –A hospital based cross sectional study - Fernando, MMPSC (Springer Science and Business Media LLC, 2023)
10.1186/s12879-017-2250-y